Computation Offloading – an Effective Approach to Enhance Smartphone Capabilities - Muhammad Wasif, Nabeel Qureshi; Abdullah, Embong (2015)

(untitled)
Mobile technology is now an integral part of our daily life. The main factor of its larger acceptance is its rapidly changing features, convenient to carry, easiest way to communicate, internet connectivity and multiple applications availability. The mobile ecosystem is blooming with smart phones and tablets to be the main driver of growth.